2019
DOI: 10.1525/mp.2019.36.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Tone Profiles of Isolated Musical Chords: Psychoacoustic Versus Cognitive Models

Abstract: We investigated perception of virtual pitches at missing fundamentals (MFs) in musical chords of three chromas (simultaneous trichords). Tone profiles for major, minor, diminished, augmented, suspended, and four other trichords of octave-complex tones were determined. In Experiment 1, 40 musicians rated how well a tone went with a preceding chord; in Experiment 2, whether the tone was in the chord. Mean ratings for nine non-chord tones were compared with predictions of four models: MFs, diatonicity, 5th-interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 68 publications
(97 reference statements)
0
11
0
1
Order By: Relevance
“…It has been proposed that chord roots have a psychological basis in pitch perception (Parncutt, 1988;Terhardt, 1974Terhardt, , 1982 empirical work indeed supports the notion that chord roots correspond to chord tones with particularly high perceptual salience, and that this perceptual salience can be predicted by computational models of pitch detection (Parncutt et al, 2019).…”
Section: Chord Rootsmentioning
confidence: 92%
“…It has been proposed that chord roots have a psychological basis in pitch perception (Parncutt, 1988;Terhardt, 1974Terhardt, , 1982 empirical work indeed supports the notion that chord roots correspond to chord tones with particularly high perceptual salience, and that this perceptual salience can be predicted by computational models of pitch detection (Parncutt et al, 2019).…”
Section: Chord Rootsmentioning
confidence: 92%
“…In the present study, we counted how often chromas immediately preceded and followed sonorities in musical scores. These prevalence profiles may be considered analogous to Experiment 1 of Parncutt et al (2019), in which listeners heard a chord followed by a tone and indicated how well it went with the chord. The resultant goodnessof-fit profiles depended in different ways on diatonic/fifth relations, missing fundamentals, and completion tones.…”
Section: Introductionmentioning
confidence: 96%
“…The analysis focused on the nine non-chord chromas in the 12-tone chromatic scale. Experiment 2 of Parncutt et al (2019) provided evidence for missing fundamental perception among non-chord chromas. All findings were limited to Western-enculturated listeners.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations